Gene Variability in Immunoregulatory Factors in Patients with Chronic Periodontitis and Diabetes Mellitus - P. Bořilová Linhartová; S. Valová; J. Kaštovský; H. Poskerová; J. Vokurka; A. Fassmann; L. Izakovičová Hollá (Czech Dental Chamber, 2015)
Introduction and aim of study: Genetic predispositions play an important role in the etiopathogenesis of periodontal diseases (CP) and diabetes mellitus (DM). Recent studies have also proven a bidirectional interrelationship between these conditions. The immunoregulatory factors, including signal peptides, so called cytokines, are considered as candidate genes for both of these diseases. The aim of our study was to analyse polymorphisms in selected cytokines, namely in the interleukin-1 (IL-1) gene cluster and IL-6 gene, in patients with CP and with/without DM and compare them with the healthy population. Methods: 590 subjects were enrolled in this case-control study: 226 healthy/non-periodontitis subjects, 248 patients only with CP, 36 patients with CP and type 1 DM (T1DM), 80 patients with CP and type 2 DM (T2DM). For genotyping methods based on polymerase chain reaction (PCR) and subsequent restriction analysis were used. Results: The allele and genotype frequencies of the studied polymorphisms, except for a variant in the IL-1B gene, did not differ significantly between the groups of patients and healthy controls. However, in the IL-1 gene cluster, a protective haplotype in CP and risk haplotypes for CP in patients with T2DM or with T1DM were found. In addition, in the IL-6 gene, a significant difference in GGG haplotype frequencies between the groups of patients with CP and healthy controls was identified. Conclusion: Our results suggest, that contrary to analyses of individual polymorphisms, different haplotypes in the IL-1 gene cluster and IL-6 gene promoter may affect the risk for CP development in patients with/without DM in Czech population. We assume that the determination of haplotypes may have a better predictive value than study of individual allele and genotype frequencies and it should be preferred in genetic analysis of complex diseases.